Anti-elastase and anti-hyaluronidase activity of phosvitin isolated from hen egg yolk. Issue 1 (2nd January 2020) - Lee, J. H.; Moon, S. H.; Hong, Y.; Ahn, D. U.; Paik, H.-D.
ABSTRACT: 1. Phosvitin, a major phosphoprotein found in egg yolk, has strong antioxidant activity. Activation of elastase, collagenase, and hyaluronidase by reactive oxygen species are related to the degradation of ECM and skin aging. The objective of this study was to determine the anti-elastase and anti-hyaluronidase activity of phosvitin. 2. Elastase from porcine pancreas and hyaluronidase from bovine testes were used to study the inhibitory activity of phosvitin. To elucidate the mechanism of enzyme inhibition, a Lineweaver-Burk plot was constructed. 3. Phosvitin inhibited elastase and hyaluronidase activity in a dose-dependent manner. The IC50 value of phosvitin was 31.6 μg/ml and 1, 270 μg/ml against elastase and hyaluronidase, respectively. The analysis of elastase and hyaluronidase kinetics indicated that the apparent Michaelis constant (app Km ) was increased by phosvitin but the Vmax value was not affected. 4. In conclusion, phosvitin exhibited competitive inhibitory activity against elastase and hyaluronidase. Thus, phosvitin could be used as a natural anti-aging agent in the cosmetics industry.